HUBUNGAN ASUPAN ASAM LEMAK OMEGA-3 DENGAN TEKANAN DARAH PADA DIABETES MELLITUS TIPE 2 - Ajeng Annisa Putri; Alvina Alvina (Jurnal Akta Trimedika, 2024)
Diabetes Mellitus (DM) is a metabolic disorder characterized by hyperglycemia as a result of pancreatic disorders in producing  hormone insulin or insulin resistance. Type 2 DM is the most common type of diabetes in Indonesia. Based on epidemiological data, DM is associated with increased morbidity and mortality rates. Diabetes is also associated with the incidence of hypertension. There are nutrients that play a role  blood pressure stable, one of which is omega 3 fatty acids. This research was conducted to determine a relationship between omega 3 fatty acids and blood pressure in type 2 DM. The design of this study was cross-sectional. 70 respondents consisting of 23 male respondents and 47 female respondents. Data were collected through interviews with respondents using the Semi Quantitative Food Frequency Questionnaire and blood pressure measurements. The statistical test uses Chi-square with significance p<0.05. In this study, there were more women, the majority aged 46-65 years, DM less than 5 years, normal blood pressure and good intake of omega 3 fatty acids. The results of  analysis showed that  was no significant relationship between omega 3 fatty acids and blood pressure in type 2 DM (p=0.270). Conclusion: There is no relationship between omega 3 fatty acids and blood pressure in type 2 DM.